School Violence: The Role of Parental and Community Involvement. (2nd October 2017) - Lesneskie, Eric; Block, Steven
ABSTRACT: This study utilizes the School Survey on Crime and Safety to identify variables that predict lower levels of violence from four domains: school security, school climate, parental involvement, and community involvement. Negative binomial regression was performed and the findings indicate that statistically significant results come from all four domains. When modifying the sample to include only schools that offer some form of parental involvement opportunities, schools with greater parental volunteering and participation in subject area events experience reduced levels of violence. Implications from this analysis include developing creative methods for greater parental input in school activities.